Illumination control system for tissue culture of plant - LIN MIN (2018)
The invention relates to the technical field of plant tissue culture parameter control, and specifically relates to an illumination control system for tissue culture of plant. The system comprises a central processor, a communication module, an input module, an illumination detection module, a signal conditioning module, a signal amplification module, an LED illumination module, a display module,and a power supply module. The system comprises LED lamps with various colors, can provide illumination with different colors for different plants, meets various demands, and improves the practicality. Meanwhile, the system can achieve the adaptive change of illumination intensity, guarantees the culture condition of the plant, enables the growth of the plant to be good, is high in automation degree, is simple in structure, is convenient to operate, saves the labor force, and improves the work efficiency. 本发明涉及植物组培参数控制技术领域，具体涉及种植物组培用光照控制系统，包括中央处理器、通信模块、输入模块、光照度检测模块、信号调理模块、信号放大模块、LED照明组件、显示模块和电源模块。本系统包括多种颜色的LED灯，能够为不同植